Vaginal reconstruction with the Abbe-McIndoe technique in Mayer Rokitansky Kuster Hauser syndrome: a case report - Swain, Sujata; Dilip, Abarajda; Singh, Prithviraj; Satpathy, Rabi Narayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is  a rare but well discussed entity characterized by congenital aplasia of the uterus and the upper part (2/3rd) of the vagina in women with normal development of secondary sexual characteristics and a normal 46, XX karyotype. The inability to lead a normal sexual and reproductive life bears a great amount of social inhibition and psychological distress on the affected individuals. The physical inability can definitely be attended to by various non-surgical and surgical techniques leading to a free sexual life. We report a case of MRKH who underwent an Abbe-McIndoe technique with one year follow up. The patient due to social inhibition, failed to report primary amenorrhea at an earlier age. She seeked medical help at the time of marriage at the age of 30 yrs .Successful vaginal reconstruction with minimal expenditure and counselling paved the way for her marriage and satisfactory sexual life.